Problema do caixeiro viajante negociante - Souza, Quézia Emanuelly de Oliveira (2022)
In this paper, the Traveling Tradesman Problem (TTP) is proposed, a variant of the Traveling Purchaser Problem previously not described in the literature. In this problem there are a set of vertices, which act as markets, where the tradesman can buy or sell goods. Thus, he seeks to buy a certain product in one city and sell it in another, so that this operation provides profit. The purpose of the problem is to determine a Hamiltonian cycle that visits all the vertices of a subset just once, carrying out purchase and sale operations, in order to maximize the profit obtained. It is proposed a detailed description of the problem, the development of instances for it, in addition to two metaheuristics solution in order to obtain competitive results, one GRASP and one Transgenetic algorithm, which were tested in instances ranging from 50 to 350 vertices. Finally, From the results obtained, it was possible to conclude that the transgenetic approach was able to find better results than GRASP, although it required a higher processing time.